Development of WirelessHART Adapter For Control Valve Actuation - Adnan, Anas (Universiti Teknologi PETRONAS, 2016)
In the process automation industry, wireless application is quite new. Due to the flexibility offered by the wireless technology, it allows process plants to extract a more condense process information hence improving the process automation of the plant. The most common wireless protocol that is currently being commercially used and considered as the international standard is the WirelessHART. However, there is a lack of reliable infrastructure in the wireless control application especially for control valves. Hence, this project focusses on the implementation of the WirelessHART protocol in control valve actuation. An adapter consisting of a microcontroller, a 4- 20mA current loop and a WirelessHART mote will be interfaced with a Digital Valve Controller (DVC) to enable a wireless control valve actuation.